Apa Kabarmu Kartun Karikatur Indonesia? - Agni Saraswati (Ars: Jurnal Seni Rupa dan Desain, 2011)
Caricature is a kind of picture or a mockery cartoon which containing message or insinuation formed by deformation process to the original figure. Good caricature contained satire, distortion and ethics with usage of word or even without word at all. In real life, caricature become one of media alternative of protesting and criticize situation.Keywords: caricature, mockery cartoon, insinuation, satire